1988
DOI: 10.1159/000195516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Renal Failure on Respiratory Muscle Strength

Abstract: In 10 patients with chronic renal failure (CRF), undergoing hemodialysis, we studied respiratory muscle strength and endurance. The data obtained was compared with those acquired from 10 age-, sex-, weight- and height-matched normal volunteers. Maximal static inspiratory pressures (PImax) measured at residual volume and maximal static expiratory pressures (PEmax) measured at total lung capacity were significantly lower in the CRF group, 58.2 ± (SD)24.9 and 50.8 ± (SD)24.2% of predicted, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
7

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 9 publications
3
36
2
7
Order By: Relevance
“…In fact, in two studies, it was demonstrated that CRF patients have significantly decreased respiratory muscle strength. (4,5) In another study, MIP was also found to be decreased after hemodialysis sessions. (19) The results of those studies were not replicated in our study, possibly due to differences in duration of hemodialysis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, in two studies, it was demonstrated that CRF patients have significantly decreased respiratory muscle strength. (4,5) In another study, MIP was also found to be decreased after hemodialysis sessions. (19) The results of those studies were not replicated in our study, possibly due to differences in duration of hemodialysis.…”
Section: Discussionmentioning
confidence: 89%
“…(4) When compared to healthy individuals, CRF patients also present decreased endurance and decreased respiratory muscle strength. (4,5) In addition to decreased pulmonary function and decreased respiratory muscle strength, CRF patients on hemodialysis present weight fluctuation due to body fluid overload in the interdialytic period. (6) This overload, together with a potential increase in pulmonary capillary permeability, can result in pulmonary edema and pleural effusion, (7,8) abnormalities that could explain-at least in part-the decrease in pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, pharyngeal narrowing in ESRD patients may be related to reduced lung volume, as reflected by the smaller observed ERV (table 4). Respiratory muscle weakness has been described in patients with ESRD [22], which could decrease FRC by reducing chest wall expansion. Alternatively, FRC may be reduced by pulmonary oedema associated with fluid overload, which is common in ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies 33,35 have reported that patients with CKD showed significantly reduced PI max , but a significant improvement of that pressure was observed after HD. Those results are partially in accordance with those obtained in the present investigation, in which a significant impairment in PI max values was observed in patients with CKD as compared with those in a normal population.…”
Section: Mean ±Standard Error ±Sd Mean ±Standard Error ±Sdmentioning
confidence: 98%